Two-bit heroes. (Economist, 1996)
Reports on quantum computing, or the use of principles in quantum mechanics to make programming easier and computer performance more efficient. Research currently underway at the California Institute of Technology in Pasadena and at the National Institute of Science and Technology (NIST) in Boulder, Colorado; Boolean algebra.